2022 International Power Electronics Conference (IPEC-Himeji 2022- ECCE Asia) 2022
DOI: 10.23919/ipec-himeji2022-ecce53331.2022.9806839
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Performance Verification of the FS-MPC Algorithm Applied to the Matrix Converter

Abstract: In recent publications statistical model checking (SMC) has been proposed as a method for verifying the performance of finite-set model predictive control (FS-MPC) algorithms applied to power electronics converters. SMC is a powerful method originating from statistics, which can provide statistical evidence of a system's performance in a stochastic environment. In this paper, SMC is applied to a direct matrix converter, which operates in a grid with different harmonic distortion levels and voltage sags. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…How high is the robustness of the trained network to model uncertainties? In [14] it was demonstrated that FS-MPC algorithm shows a high robustness to model parameter mismatch, the question is if this robustness is also inherited by the trained ANN controller. In the following section these questions will be answered by performing a HIL verification of the trained ANN controller.…”
Section: Introductionmentioning
confidence: 99%
“…How high is the robustness of the trained network to model uncertainties? In [14] it was demonstrated that FS-MPC algorithm shows a high robustness to model parameter mismatch, the question is if this robustness is also inherited by the trained ANN controller. In the following section these questions will be answered by performing a HIL verification of the trained ANN controller.…”
Section: Introductionmentioning
confidence: 99%